2020
DOI: 10.1002/celc.202000089
|View full text |Cite
|
Sign up to set email alerts
|

System Design Rules for Intensifying the Electrochemical Reduction of CO2 to CO on Ag Nanoparticles

Abstract: Electroreduction of CO 2 (eCO 2 RR) is a potentially sustainable approach for carbon-based chemical production. Despite significant progress, performing eCO 2 RR economically at scale is challenging. Here we report meeting key technoeconomic benchmarks simultaneously through electrolyte engineering and process optimization. A systematic flow electrolysis studyperforming eCO 2 RR to CO on Ag nanoparticles as a function of electrolyte composition (cations, anions), electrolyte concentration, electrolyte flow rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
143
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 112 publications
(157 citation statements)
references
References 99 publications
4
143
0
Order By: Relevance
“…These trends are similar to experimental results obtained from gas-fed CO 2 electrolyzers. [32,36] The next step was to determine whether the cation identity affects the rate of i-CO 2 formation [Equation (2)], the rate of the CO2RR [Equation (3)], or both. To resolve this question, we quantified the rates of i-CO 2 formation for each [MHCO 3 ] (M = Li, Na, K, Cs) electrolyte at a constant applied current density of 100 mA cm À 2 (Figure 3a).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These trends are similar to experimental results obtained from gas-fed CO 2 electrolyzers. [32,36] The next step was to determine whether the cation identity affects the rate of i-CO 2 formation [Equation (2)], the rate of the CO2RR [Equation (3)], or both. To resolve this question, we quantified the rates of i-CO 2 formation for each [MHCO 3 ] (M = Li, Na, K, Cs) electrolyte at a constant applied current density of 100 mA cm À 2 (Figure 3a).…”
Section: Resultsmentioning
confidence: 99%
“…[16,[18][19][20] The CO2RR studies that use gaseous CO 2 or CO 2 dissolved in water as feedstocks have shown that increasing the ionic size of the alkali-metal cation from Li + to Cs + increases CO2RR product selectivity. [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] This CO2RR literature, however, provides little direction as to how to optimize the composition of a bicarbonate feedstock to enhance CO formation rates in a bicarbonate electrolyzer. Some reports have shown that the cation identity influences the local pH [and therefore acid-base reactions such as Equation (2)], [23,24,[28][29][30] while others have shown that the cation affects the CO2RR [Equation (3)] by modulating the electrical double-layer at the silver cathode surface.…”
Section: Water Dissociation In the Bpmmentioning
confidence: 99%
“…Considering the results of previous studies on the promoting effect of alkali cations in electrochemical CO 2 R [37][38][39][40][41][42][43][44] , cation permeation through the membrane from the anolyte might contribute to achieving high reaction rates (this is absent in the case of water-based operation). In microfluidic electrolysers operating with liquid catholyte, alkali ions are inherently present around the cathode catalyst, which might (partly) explain why these systems outperform their zero-gap counterparts in terms of the achievable current densities 13,45 . Furthermore, a long activation period (~60 min) was observed for zero-gap cells operated with dilute alkaline anolytes (Supplementary Fig.…”
Section: Activating the Cathode Catalyst By Infusion With Alkali Cation-containing Solutionsmentioning
confidence: 99%
“…In microfluidic cells, highly alkaline conditions allow high current density (>1 A cm −2 ) production of CO 13 , ethylene 14,15 , methane 16,17 and multi-carbon products 18 . While these results are very promising, the scale-up of microfluidic electrolysers seems challenging 2 .…”
mentioning
confidence: 99%
“…Instead, the overall trend is that zero-gap electrolyzers tend to operate with smaller current densities, but the total cell voltage and single pass conversion values are similar to studies using liquid catholyte. 7,[12][13][14][15][16][17] In general, j CO remains below 400 mA cm À2 in most studies with zero-gap electrolyzers (there is only one single report on j CO over 400 mA cm À2 employing the Sustainion s membrane 18 ). Since very similar cathode GDEs (containing Ag nanoparticle catalysts), anode and anolytes are employed in most studies (irrespective of the cell architecture), we can assume that something else has been limiting the achievable current density in the zero-gap design.…”
Section: Introductionmentioning
confidence: 99%